Twarze terroryzmu religijnego. Od maski do selfie (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The title of this article promises to focus on religion as a motivational drive for terrorism. However, I am far from thoughtless replicating the term ’religious terrorism’. It mistakenly suggests some presumed obviousness in defining the problem. Meanwhile, in recent decades the so-called critical terrorism studies have repeatedly proved that such labeling generates problems instead of explaining them. Cultural visual studies show that religious terrorism has many faces.